The Quality Assurance of Islamic Boarding School based on Total Quality Management (TQM) - Ijah, Titin; Sumaryanto Florentinus, Totok; Made Sudana, I (Educational Management, 2021)
The education quality assurance of Darul Arafah Raya Islamic Boarding School based on TQM is a deserved breakthrough to improve its education quality. This research aims to describe and analyze the Islamic boarding school's quality assurance improvements based on TQM. It is done by involving the whole concerning parties to reach the vision and mission of Darul Arafah Raya Islamic boarding school. This research applied a case study qualitative approach. The data were collected by interview, observation, and documentation. The research data validity was obtained from triangulation and the researcher’s diligence improvements. The applied analyzing technique was Miles and Huberman interactive model. With a purpose to guarantee the Islamic boarding school's quality, the finding showed that TQM implementations were not applied to all TQM functions. The main focus was only on curriculum quality improvement. Darul Arafah Raya’s TQM implementations did not have specific and structured parts. Its leader had essential roles to involve and empower the whole teams to guarantee the Islamic boarding school's quality based on TQM and with proper managerial skills. It was also crucial to participate in monitoring each activity. Thus, it could support the education customers' necessities (the Islamic students', their representatives or parent, and the surrounding society).